Learning Arabic for Elementary Schools During the Covid-19 Outbreak / Pembelajaran Bahasa Arab untuk Madrasah Ibtidaiyah Pada Masa Wabah Covid-19 - Nabilla Nurbaiti Zulaini; Nuril Mufidah; Nur Kholis; Muhammad Afif Amrulloh (STAI Ma'had Aly Al-Hikam Malang, 2020)
The Covid 19 emergency outbreak was imposed by the Indonesian government, and the minister of education launched a study from home since March 2020. Learning is done online / in accordance with government regulations to break the spread of the epidemic. In general, low-grade MI children still have problems recognizing Arabic letters. This will cause students difficulty learning Arabic subjects. This study describes the teaching of Arabic for elementary schools / MI, with research subjects in the class 3A MIN 3 Janti, Ponorogo-Indonesia totaling 24 students, and Arabic language teaching teachers. Data collection methods used observation and interviews to determine the teaching methods used, and the constraints faced by teachers and students. The results showed that online Arabic teaching for MI used the lecture method. The obstacles faced by teachers are the lack of opportunities to monitor one by one student and many students who cannot attend while the obstacle for students is the lack of understanding of the lessons conveyed by the teacher, internet network connections that do not support.Â